Performances evaluation of epoxy asphalt mixture containing snow-melting agent. (30th November 2017) - Min, Zhaohui; Xia, Yuyu; Li, Xiaochen; Tao, Zan
Highlights: The snow-melting agent influences epoxy asphalt mixture performances slightly. The snow-melting agent in epoxy asphalt mixture releases slowly compared to SBS. The epoxy asphalt snow-melting mixture provides preferable snow melting performance. The epoxy asphalt snow-melting mixture has a long snow melting life. Abstract: The performance degradation of the asphalt mixture blended with the snow-melting agent can inevitably occur although it can be relieved by adding the high viscosity modifier or Nanopowder. The thermosetting epoxy asphalt binder, different from the conventional thermoplastic asphalt as SBS modified asphalt, was adopted in this research to solve this problem. Experiments were carried out to test the road engineering performances, conductivity, deicing and snow melting performances of epoxy asphalt mixture with the snow-melting agent content of 6%, 7% and 8%, substituting the equivalent amount of mineral filler, and then the results were compared with SBS modified asphalt mixture. The results show that snow-melting agent has a slight influence on the engineering performance of epoxy asphalt mixture. With snow-melting agent content or environmental temperature rising, the snow-melting agent release amount and rate of epoxy asphalt mixture increase, but are lower than those of SBS modified asphalt mixture under the same condition. The epoxy asphalt mixture with snow-melting agent can provide preferable snow melting performance and low ice adhesion. This thermosetting mixture with snow-melting agent possesses engineering application potential due to its excellent performance and long snow melting life.